2002
DOI: 10.1046/j.1365-8711.2002.05425.x
|View full text |Cite
|
Sign up to set email alerts
|

All-sky astrophysical component separation with Fast Independent Component Analysis (FASTICA)

Abstract: A B S T R A C TWe present a new, fast, algorithm for the separation of astrophysical components superposed in maps of the sky. The algorithm, based on the Independent Component Analysis (ICA) technique, is aimed at recovering both the spatial pattern and the frequency scalings of the emissions from statistically independent astrophysical processes, present along the line-ofsight, from multi-frequency observations, without any a priori assumption on properties of the components to be separated, except that all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 18 publications
3
166
0
1
Order By: Relevance
“…6). A dominating CMB component is a good approximation to real sky maps at least at medium and high Galactic latitudes where the effects of diffuse foregrounds from our Galaxy can be neglected (see Maino et al 2002, and references therein). The PSFs used in the experiments are Gaussians with FWHM similar to that expected for the PLANCK-LFI instrument.…”
Section: Numerical Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…6). A dominating CMB component is a good approximation to real sky maps at least at medium and high Galactic latitudes where the effects of diffuse foregrounds from our Galaxy can be neglected (see Maino et al 2002, and references therein). The PSFs used in the experiments are Gaussians with FWHM similar to that expected for the PLANCK-LFI instrument.…”
Section: Numerical Experimentsmentioning
confidence: 98%
“…For example, available prior information about the signals can be used in a regularised inversion via Wiener filtering and maximum entropy methods, either on small sky patches (Hobson et al 1998) or on the whole sky (Bouchet & Gispert 1999;Stolyarov et al 2002). It has been shown that under certain independence assumption on the signals, the map-operating algorithms based on Independent Component Analysis (ICA) techniques can be applied on sky patches (Baccigalupi et al 2000) as well as on the whole sky (Maino et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties have led to a surge in ICA-based analysis methods in current cosmology and extra-galactic astronomy. Here ICA is used to separate the cosmic microwave background (CMB) or signatures of distant galaxies from their galactic foregrounds (e.g., Stivoli et al 2006;Maino et al 2002Maino et al , 2007Wang et al 2010). Aumont & Macías-Pérez (2007) furthermore separate instrumental noise from the desired astrophysical signal.…”
Section: Background: the Cocktail Party Problemmentioning
confidence: 99%
“…Several techniques have become available; from simple Galaxy masking of heavily contaminated regions and point sources (e.g. Mejía et al 2005) to the novel approaches of component separation and foreground removal (Hobson et al 1998;Maino et al 2002;Delabrouille et al 2003Delabrouille et al , 2009Eriksen et al 2004Eriksen et al , 2006Eriksen et al , 2008Bonaldi et al 2006;Cardoso et al 2008;Leach et al 2008;Stompor et al 2009;Ricciardi et al 2010;Fernández-Cobos et al 2012;Planck Collaboration 2013c), which exploit the spectral and spatial diversity of the different astrophysical and cosmological components. The multi-frequency design of the WMAP mission had already revealed an impressive picture of unprecedented precision of the CMB at 23 GHz, 33 GHz, 41 GHz, 61 GHz and 94 GHz (Hinshaw et al , 2012Bennett et al 2012); whereas the Planck mission, with its higher angular resolution and superb sensitivity at 30 GHz,44 GHz,70 GHz,100 GHz,143 GHz,217 GHz,353 GHz,545 GHz,and 857 GHz has, at the time of writing, made available an overwhelming set of results that push the standards of cosmological and astrophysical research to a state-of-the-art level (Planck Collaboration 2013b).…”
Section: Cmb Contaminationmentioning
confidence: 99%